Effect of Media Variation on the Induction and Phytochemical Profile of Callus in Two Varieties of Cat's Whiskers (Orthosiphon aristatus Blume Miq) - Fahrauk Faramayuda; Akhirul Kahfi Syam; Totik Sri Mariani; Elfahmi; Sukrasno (HAYATI Journal of Biosciences, 2023)
The levels of rosmarinic acid and sinensetin in purple and white-purple varieties of Orthosiphon aristatus, cat's whiskers, can be increased using modified in vitro culture. This work focused on callus induction of the purple and white-purple variety of cat's whiskers grown on Gamborg (B5) and CHU (N6) with the addition of growth regulators 2,4-dichlorophenoxyacetis acid. Our observation suggested that the callus could grow within three weeks and produce rosmarinic acid and sinensetin. The level of sinensetin from various extraction methods is relatively low; in contrast, the rosmarinic acid from purple callus was detected at about 5% w/w, while the white-purple variety was around 2% w/w. The results of this study also provided new information on the basic media other than MS that can grow cat's whiskers callus while producing active compounds.